Current Approaches in the Diagnosis and Treatment of Canine Otitis - Tešin, N; Kovačević, Z (Journal of the Hellenic Veterinary Medical Society, 2025)
As a disease with high prevalence in canine, otitis externa (OE) requires a summary of its diagnosis and treatment. Since antimicrobials are predominantly used in OE treatment, their prudent use must be in focus due to significant impact on the spread and development on the antimicrobial resistance (AMR). Furthermore, as AMR is constantly increasing, further studies are required to create novel treatment approaches against causative agents. Therefore, new alternative approaches to antimicrobials and antifungals were investigated to discover an effective approach to OE treatment. In addition to diagnosis and conventional treatment, this review aimed to summarize the findings of various publications related to the usage of essential oils against OE associated pathogens. While there are very few in vivo trials, numerous in vitro studies have demonstrated the effectiveness of essential oils and their potential application in OE treatment. New alternative approaches are leading toward the development of new treatment objectives and alternatives.